2004
DOI: 10.1038/sj.cgt.7700714
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder cancer treatment using adenovirus expressing the HGF/NK4 gene in a peritoneal implantation model

Abstract: Gallbladder cancer cells are stimulated by hepatocyte growth factor (HGF) in vitro and in vivo. We constructed an adenovirus vector, AdCMV.NK4, carrying the HGF antagonist HGF/NK4 (NK4) and evaluated whether or not this vector can suppress the peritoneal implantation of gallbladder cancer in a novel peritoneal injury mouse model. A human gallbladder cancer cell line (GBd1) and human peritoneal mesothelial cells infected with the adenovirus vector produced a substantial level of NK4 protein. An invasion of GB-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…[28][29][30][31][32] These data indicate that NK4 is certainly effective for various types of carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32] These data indicate that NK4 is certainly effective for various types of carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients tend to demonstrate unresectable disease at the time of surgical evaluation because of the rapid invasive and metastatic progression of this cancer. Therefore, surgical treatment becomes ineffective and new treatments, such as gene therapy, are desperately needed (Dong et al, 2011a;Fukuda et al, 2003;Tanaka et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…39 So far, NK4 gene therapy has demonstrated efficacy in tumor models in which the involvement of the HGF-cMET signaling pathway in pathogenesis has been clearly established. [8][9][10][11][12][13][14][15][16][17][18][19][20] Based on the multifunctional properties of NK4 on various growth factors, 3,4,12,40 we propose that NK4 gene therapy would have therapeutic value for a wider range of tumors than only cMET overexpressing carcinomas. However, application of NK4 gene therapy to specific tumor types such as HCC for which the effect of the HGF-cMET signaling is less explicit or may even be inhibitory on carcinogenesis [32][33][34] needed further assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] NK4, which consists of the N-terminal hairpin domain and the four subsequent kringle domains of HGF, competitively inhibits the multiple biological activities of HGF through binding to cMET and is suggested to have a broad antiangiogenic activity through its kringle domain structure. 3,4,7 Previous in vivo studies confirmed therapeutic efficacy of NK4 gene therapy for glioblastoma, prostate, breast, gastric, pancreatic, gall bladder and colon cancers [8][9][10][11][12][13][14][15][16][17][18][19][20] and recommended further preclinical evaluation of NK4 gene therapy as anticancer agent. However, NK4 gene therapy for treatment of HCC could be argued against because the antitumor effects of NK4 in part rely on its antagonistic activity to HGF 3 and the role of the HGF-cMET system in hepatocarcinogenesis has not been clearly established.…”
mentioning
confidence: 99%